2009
DOI: 10.1186/1471-2407-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Two mechanisms of the enhanced antibody-dependent cellular cytotoxicity (ADCC) efficacy of non-fucosylated therapeutic antibodies in human blood

Abstract: BackgroundAntibody-dependent cellular cytotoxicity (ADCC) has recently been identified as one of the critical mechanisms underlying the clinical efficacy of therapeutic antibodies, especially anticancer antibodies. Therapeutic antibodies fully lacking the core fucose of the Fc oligosaccharides have been found to exhibit much higher ADCC in humans than their fucosylated counterparts. However, data which show how fully non-fucosylated antibodies achieve such a high ADCC in human whole blood have not yet been dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…Previous studies have shown that changing the glycosylation pattern of the Fc portion of antibodies can influence their ability to elicit effector function by enhancing their binding affinity to FcγRIIIa on human immune cells. 14,27 We saw similar enhanced affinity to FcγRIIIa with SMIP-016 GV (Fig. 1C).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have shown that changing the glycosylation pattern of the Fc portion of antibodies can influence their ability to elicit effector function by enhancing their binding affinity to FcγRIIIa on human immune cells. 14,27 We saw similar enhanced affinity to FcγRIIIa with SMIP-016 GV (Fig. 1C).…”
Section: Resultssupporting
confidence: 57%
“…Radio-labeled mouse monoclonal antibodies Fc oligosaccharides elicit high ADCC responses by two mechanisms. 14 On the effector cell side, afucosylated anti-CD20 antibodies were less inhibited by human plasma IgG. On the target cells, cells treated with non-fucosylated anti-CD20 antibodies showed markedly stronger binding to NK cells than fucosylated anti-CD20.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…38 Defucosylation of Fc glycans could also circumvent the inhibitory effects both of plasma IgG on the binding of FcgRIIIa on NK cells and of fucosylated counterparts on the binding of the antigen on target cells. [39][40][41] Importantly, J6M0-mcMMAF and naked J6M0 significantly enhanced ADCC in vitro and anti-MM activity in vivo, when compared with its fucosylated normal Fc version. To our knowledge, J6M0-mcMMAF would be the first therapeutic ADC with defucosylated oligosaccharides entering clinical trials in MM.…”
Section: Discussionmentioning
confidence: 91%
“…It is not surprising that increasing effector functions by means of Fc-glycosylation engineering has gained considerable interest 196 . As a consequence, the pharmaceutical industry has allocated remarkable research efforts to glycan engineering, aiming to increase ADCC of mAbs, in particular by limiting core fucosylation 48,65,91,[308][309][310][311][312][313] . Many reports have described the significant increase of ADCC whenever the fucose attachment to the glycan backbone was precluded 42,196,308,312 .…”
Section: Introductionmentioning
confidence: 99%